ABCG2 Protects Kidney Side Population Cells from Hypoxia/Reoxygenation Injury through Activation of the MEK/ERK Pathway. Issue 10 (October 2013) - Liu, Wei-Hui; Liu, Hong-Bao; Gao, Da-Kuan; Ge, Guan-Qun; Zhang, Peng; Sun, Shi-Ren; Wang, Han-Min; Liu, Shui-Bing
Breast cancer resistance protein 1 (BCRP1/ABCG2) is used to identify the side population (SP) within a population of cells, which is enriched for stem and progenitor cells in different tissues. Here, we investigated the role of extracellular signal-regulated kinase (ERK) 1/2 in the signaling mechanisms underlying ischemic/hypoxic conditions in kidney SP cells. Kidney SP cells were isolated using Hoechst 33342 dye-mediated fluorescein-activated cell sorting and then incubated under hypoxia/reoxygenation (H/R) with or without verapamil, a selective BCRP1/ABCG2 inhibitor. ABCG2 expression, ERK activity, cell viability, metabolic activity, and membrane damage were tested after H/R treatment. To evaluate the role of ERK 1/2 on the expression and function of ABCG2, the expression of mitogen-activated protein kinase (MAPK)/ERK kinase (MEK), which preferentially activates ERK, was upregulated by transfection with the recombinant sense expression vector pcDNA3.1-MEK and downregulated by pretreatment with U0126, a specific MEK inhibitor. We found that hypoxia activated ERK activity in the kidney SP cells but not in non-SP cells both in vitro and in vivo. Overexpression of MEK mimicked hypoxia-induced ABCG2 expression. Contrarily, U0126 inhibited hypoxia- and MEK-upregulated ABCG2 expression. Furthermore, H/R induced significant increases in nuclear, metabolic, and membrane damage in both SP cells and non-SP cells; however, this H/R-induced cytotoxicity was much more severe in non-SP cells than in SP cells. Notably, the viability of kidney SP cells was enhanced by MEK overexpression and inhibited by U0126. Verapamil treatment reversed MEK-induced viability of kidney SP cells. When administered systemically into animals with renal ischemia/reperfusion injury, the SP cells significantly improved renal function, accelerated mitogenic response, and reduced cell apoptosis. However, this improved therapeutic potential of SP cells was significantly reduced by pretreatment with verapamil. Collectively, these findings provide evidence for a crucial role for the MEK/ERK-ABCG2 pathway in protecting kidney SP cells from ischemic/hypoxic injury.